Increased glycosylphosphatidylinositol‐anchored protein‐deficient granulocytes define a benign subset of bone marrow failures in patients with trisomy 8. (4th February 2015) - Hosokawa, Kohei; Sugimori, Naomi; Katagiri, Takamasa; Sasaki, Yumi; Saito, Chizuru; Seiki, Yu; Mochizuki, Kanako; Yamazaki, Hirohito; Takami, Akiyoshi; Nakao, Shinji
Abstract Trisomy 8 (+8), one of the most common chromosomal abnormalities found in patients with myelodysplastic syndromes (MDS), is occasionally seen in patients with otherwise typical aplastic anemia (AA). Although some studies have indicated that the presence of +8 is associated with the immune pathophysiology of bone marrow (BM) failure, its pathophysiology may be heterogeneous. We studied 53 patients (22 with AA and 31 with low‐risk MDS) with +8 for the presence of increased glycosylphosphatidylinositol‐anchored protein‐deficient (GPI‐AP−) cells, their response to immunosuppressive therapy (IST), and their prognosis. A significant increase in the percentage of GPI‐AP− cells was found in 14 (26%) of the 53 patients. Of the 26 patients who received IST, including nine with increased GPI‐AP− cells and 17 without increased GPI‐AP− cells, 14 (88% with increased GPI‐AP− cells and 41% without increased GPI‐AP− cells) improved. The overall and event‐free survival rates of the +8 patients with and without increased GPI‐AP− cells at 5 yr were 100% and 100% and 59% and 57%, respectively. Examining the peripheral blood for the presence of increased GPI‐AP− cells may thus be helpful for choosing the optimal treatment for +8 patients with AA or low‐risk MDS.